Seismic Performance and Cost Analysis of UHPC Tall Buildings in UAE with Ductile Coupled Shear Walls - AlHamaydeh, Mohammad (2022)
The superior mechanical characteristics of ultra-high-performance concrete (UHPC) have attracted the interest of many researchers worldwide. Researchers have attempted to perform comparative analyses on the behavior of UHPC versus conventional and high-strength concrete, with their aim being to gain more insights into the difference between different types of concrete. However, the current state-of-the-art revealed no direct comprehensive comparisons between their behaviors in ductile coupled shear walls under seismic loading. This paper explores a comprehensive side-by-side comparison in terms of seismic behavior and cost analysis for four 60-story archetype buildings. The reference building was designed using high-strength concrete with a strength of 60 MPa. The other three archetype variations incorporated three different UHPC grades: 150 MPa, 185 MPa, and 220 MPa. The plan configuration and the lateral force-resisting system (LFRS) were chosen according to the most common practice in the UAE. The main objective is to report the effect of UHPC on the LFRS (ductile coupled shear walls). Moreover, a simplified initial cost analysis (materials and labor) design was performed. The findings of this paper indicate that the use of UHPC is capable of improving the seismic performance behavior of the lateral system as well as reducing the total initial costs.